Incorporating the customer experience along different iterative cycles of service design - Sarmento, Teresa (2015)
The creative transition from understanding the customer experience to defining the service solution, from current situation to preferred future, is central to Service Design. However, the incorporation of customer experience factors can change along the different iterative cycles of service design. To address this challenge, this paper presents the results of a study of how the path of customer experience was followed, studied and incorporated along a mobile service development. Three iterative Service Design cycles enabled a holistic vision of the service and raised ‘customer experience’ awareness on the development team. Following a design research approach, experience factors were actively taken into account and incorporated along ideation and implementations cycles involving a total of 61 interviews. The research work contributes to Service Design by providing a global vision of the experiential changes, especially in mobile and technology based services. It describes the reframed situations working with experiences at each cycle of design, and making use of service design tools and methods at each moment.